2014
DOI: 10.3892/ol.2014.2361
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-microRNA-101 suppresses migration and invasion by targeting Rac1 in thyroid cancer cells

Abstract: MicroRNAs (miRNAs) are 22- to 25-nucleotide non-coding RNA molecules that function as negative regulators of gene expression. In previous years, increasing evidence has arisen implicating the involvement of miRNAs in carcinogenesis. In previous studies, the role of miRNA-101 (miR-101) in tumors has been identified as a tumor suppressor and, until now, the role of miR-101 and Rac1 in thyroid cancer has remained undefined. This study revealed that miR-101 is significantly downregulated in papillary thyroid carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…miRNAs can regulate gene expression by targeting complementary sequences primarily located on the 3 0 untranslated regions (UTRs) of target genes [11][12][13][14]. For example, microRNA (miR)-101 targets Rac1 to suppress the migration and invasion of thyroid cancer cells [15], and miR-708 and miR-31 regulate proliferation, apoptosis, and invasion of colorectal cancer cells [16]. Let-7 is downregulated in human lung cancer, and this downregulation is associated with shortened survival in these patients; however, restoration of Let-7 expression induces growth inhibition of lung cancer cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs can regulate gene expression by targeting complementary sequences primarily located on the 3 0 untranslated regions (UTRs) of target genes [11][12][13][14]. For example, microRNA (miR)-101 targets Rac1 to suppress the migration and invasion of thyroid cancer cells [15], and miR-708 and miR-31 regulate proliferation, apoptosis, and invasion of colorectal cancer cells [16]. Let-7 is downregulated in human lung cancer, and this downregulation is associated with shortened survival in these patients; however, restoration of Let-7 expression induces growth inhibition of lung cancer cells [17].…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation is required to clarify whether the osteogenic differentiation is regulated by other miRNAs. MiR-101, frequently silenced in human cancers, has been shown to have fundamental roles in diverse cellular processes, especially in the control of proliferation and differentiation12131415. Notably, Li et al 16 reported that miR-101 may promote the osteogenic differentiation of periodontal ligament cells by targeting periodontal ligament associated protein-1 (PLAP-1/aspirin).…”
mentioning
confidence: 99%
“…These include immuno-histochemical stains, microRNAs, gene mutations/ rearrangements, and gene expression panels [5]. MicroRNAs (miRNAs) are 22-to 25-nucleotide non-coding RNA molecules that typically prohibit protein production by binding to the 3' untranslated region [UTR] of specific target mRNAs [6]. Each microRNA has the distinct capability to potentially regulate the expression of hundreds of coding genes and thereby modulate several cellular pathways including proliferation, apoptosis and stress response [7].…”
Section: Introductionmentioning
confidence: 99%